1992
DOI: 10.1093/clind/15.4.712
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Pneumonia with Severe Sequelae in an Immunocompetent Adult

Abstract: Notable complications from adenovirus pneumonia in healthy adults are rare. We report a well-documented case of adenovirus type 3 infection in a previously well adult woman that resulted in severe pulmonary complications as well as self-limited ocular, hepatic, and gastrointestinal abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 3 publications
1
18
0
Order By: Relevance
“…However, adenovirus pathogens appear to be almost ubiquitous when testing for viruses is done on otherwise healthy children with respiratory illness [64][65][66]. Young adult populations outside of the military have also been severely affected by adenovirus [67][68][69][70][71]. Vaccination against adenovirus was proposed in the past as a public health intervention for civilians [66,72,73], and the military might be well advised to partner with the civilian sector in its attempts to reestablish the development and production of adenovirus vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…However, adenovirus pathogens appear to be almost ubiquitous when testing for viruses is done on otherwise healthy children with respiratory illness [64][65][66]. Young adult populations outside of the military have also been severely affected by adenovirus [67][68][69][70][71]. Vaccination against adenovirus was proposed in the past as a public health intervention for civilians [66,72,73], and the military might be well advised to partner with the civilian sector in its attempts to reestablish the development and production of adenovirus vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric patients undergoing allogeneic stem cell transplantation are particularly prone to disseminated AdV infections, with high associated morbidity and mortality [40]. Severe systemic AdV infection can also occur in patients with acquired immune deficiency syndrome (AIDS) [41]. The adenovirus family consists of 51 known serotypes, which fall into six species, A to F [5,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus serotype 3 can cause large outbreaks (4,7,10,12,13,14) resulting in severe acute respiratory diseases (1,22). Results from the Seoul National University Children's Hospital performing viral surveillance for childhood lower respiratory tract infections (LRTIs) indicated that Ad3 and Ad7 serotypes accounted for more than half of adenoviral LRTIs, including a large nationwide epidemic of Ad7-associated pneumonia as well as annual outbreaks of LRTIs associated with Ad3 (3).…”
mentioning
confidence: 99%